Music teachers’ perceptions: the role of music education in early literacy - Holmberg, Susan D. (Kansas State University, 2010)
In the wake of No Child Left Behind Act (U.S. Department of Education, 2006), educational reforms focused on providing students with effective systematic instruction in reading skills have become a nationwide concern. Report findings from the National Reading Panel (National Institute of Child Health and Human Development, 2000), indicate the establishment of a high quality comprehensive reading curriculum must include the five key components of phonemic awareness, phonics, fluency, vocabulary, and comprehension to improve reading achievement. These essential elements, with emphasis on phonemic awareness and phonics skills beginning in pre-kindergarten, are instrumental in the acquisition of early literacy development. The purpose of this qualitative study was directed toward better understanding first grade general music teachers’ perceptions of the role of music education in the attainment of early literacy. Using a multi-site case study design to examine and present an analysis of nine public elementary school music educators from across a Midwestern state, each of which used one of the three elementary general music series currently published, resulted in this collective case study. Data indicated parallels focused on the five key reading components between music and language literacy development processes, with particular emphasis on aural discrimination skills to phonemic awareness. Further findings described the sequential sound before symbol pedagogical practice of music literacy development from the perspective of the nine general music educators to be similar to early reading skills progressions, as they experienced equivalent learning processes. Implications for the educational community and suggestions for further research were discussed.
Keywords: Music education; Education, Curriculum and Instruction (0727); Education, Early Childhood (0518); Education, Music (0522)